Mix design of concrete incorporating fine recycled concrete aggregates: A review - Stamenić, Milan (Građevinski materijali i konstrukcije, 2025)
Construction and demolition waste is one of the world's largest waste streams. Increasing the use of recycled concrete helps reduce raw material extraction, landfill disposal, and emissions. Fine recycled concrete aggregate (FRCA), produced from crushed waste concrete, retains hardened or partially hardened cement paste, which increases porosity, water absorption (WA), and angularity compared to natural sand. High WA remains a key barrier to the broader use of FRCA in recycled aggregate concrete. This review examines existing methods for determining WA and the mix-design approaches reported in the literature to compensate for FRCA's high absorption. Based on the selected studies, limitations of the analyzed methods in determining WA were identified, especially the requirements for the saturated surface condition in the dry state, and some potential improvements were suggested. Regarding concrete mix design, several proposed methods are summarized: water compensation, pre-saturation, particle packing method, and also phase mixing, citing their reported effects on workability and compressive strength of concrete with recycled aggregate. Overall, combining water compensation with staged mixing offers a practical basis for wider production of FRCA concrete. However, for successful application of this method more precise WA determination is required, which is still underinvestigated.